Survey of general practitioners' attitudes to AIDS in the North West Thames and East Anglian regions - Boyton, Rosemary (1988)
As the numbers of people suffering from human immunodeficiency virus infection and the acquired immune deficiency syndrome (AIDS) increase, so will the contribution to care required from general practice. A postal questionnaire survey was therefore carried out among general practitioners in the North West Thames and East Anglian regions to determine their attitudes to AIDS and the issues it raises for them. One hundred and thirty seven questionnaires were returned (response rate 57%) and four factors underlying the doctors' attitudes identified; these concerned disease control, general practitioner care, patient support, and perception of seriousness. There were wide divergencies of attitude among the general practitioners, younger doctors being more in line with specialist thinking on AIDS than older colleagues, and evidence of important gaps between policies advocated by AIDS specialists and bodies of opinion in general practice. Attitudes to AIDS in general practice may partly be a function of personal experience; further study is required.